[Ethnographic Study of Gay Men in Australia and New Zealand] - Appleby, George A. (1998)
Keywords: dept.swk; faculty_collection; sabbatical_report

Impact of Welfare Reform in Connecticut. - Rofuth, Todd (Fall;Social Work., 1998)
Keywords: dept.swk; faculty_collection; sabbatical_report

Empirical (qualitative) Research on Social Work Education. - Senzer, Mark (Spring;Social Work., 1998)
Keywords: dept.swk; faculty_collection; sabbatical_report

The Gender Dance in Couples Therapy - Worden, Mark; Worden, Barbara Drahus (Brooks/Cole, 1998)
Keywords: Marital psychotherapy; dept.swk; faculty_collection

Can applied science in environmental monitoring transform science education? - Holloway, S.; Rofuth, T.W.; Gruner, H.; Mimo, A. (Educational Forum, 1998)
1 citations (Crossref) [2023-10-31]
Keywords: dept.swk

Untitled - Rooney, R; Kalke, NE; Macy, J; Freddolino, P; Raymond, FB; Jacobsen, M; Siegel, E; Black, J; Hagen, C; Potts, M; Wilson, G (Journal of Social Work Education, 1998)
tex.unique-id: ISI:000073923300019
Keywords: dept.swk; ⛔ No DOI found

Alcohol Use Among Latino Males - Colon, Edgar (Alcoholism Treatment Quarterly, 1998)
This paper examines the factors surrounding the use of alcohol among Latino males. Prevention and treatment strategies for the provision of culturally competent treatment services are proposed, based on an analysis of the literature.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/168-066-382-277-325, pop00295 tex.type: [object Object]
Keywords: alcoholism; article; dept.swk; ethnic group; health care delivery; health care planning; human; incidence; preventive health service; united states

Distance learning in social work education - Siegel, Elbert; Jennings, Joanne G; Conklin, Jack; Flynn, Shelly A Napoletano (Journal of Social Work Education, 1998)
This article reports data collected from a national survey of all accredited social work programs conducted between December 1995 and February 1996. The purpose was to assess current usage of distance learning in social work education. The findings suggest that the use of distance learning has increased, and that the most prevalent issues reported by educators involve adapting instructional material for course presentation and faculty preparation. Implications of the study findings for social work education are also discussed.
75 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000072567700007, lens.org/049-049-144-684-671 tex.organization: [object Object] tex.type: [object Object] tex.unique-id: [object Object]
Keywords: dept.swk